Pendampingan Pembuatan Bahan Ajar Bagi Guru Sekolah Dasar Islam Terpadu (SDIT) Salsabila Al Muthi'in Berbasis Multimedia dengan Menggunakan Microsoft Power Point - Ayuningtyas, Astika; Honggowibowo, Anton Setiawan; Pujiastuti, Asih; Retnowati, Nurcahyani Dewi; Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Teachers are a very noble profession, because one of the teachers' tasks is to help the intellectual life of the nation. As teachers in their daily lives to educate the nation, requires the support of equipment that can be used in the teaching and learning process in the field that it has. The necessary support material may be hardware and software that can be used to compile teaching materials of interest to learners. Therefore, teachers should have the skills as educators to leverage the kmputer hardware and software correctly to create interactive educational materials in the digital age, one of the multimedia-based teaching materials using Microsoft software Power point. The purpose of teaching didactic materials for teachers is to provide teachers with skills to use the use of Microsoft Power Point to produce interactive documents that may be more interesting for student learning. Thus, the implementation of community service activities with the title